XML 문서 보안을 위한 효율적인 권한부여 방법 - 조선문(Sun-Moon Jo); 정경용(Kyung-Yong Chung) (한국콘텐츠학회 논문지, 9(8), 2009)
XML can supply the standard data type in information exchange format on a lot of data generated in running database or applied programs for a company by using the advantage that it can describe meaningful information directly. Therefore, as it becomes more and more necessary to manage and protect massive XML data in an efficient way, the development of safe XML access control techniques needs a new method. In this study access authorization policies are defined to design access control systems. The findings demonstrated that algorithm suggested in this study improved system performance which was low due to the complex authorization evaluation process in the existing access control techniques. It is consequently proved that the safe XML access control policy presented in this study is in an improved form as compared with the existing access control methods. XML은 스스로 의미 있는 정보를 기술할 수 있는 장점을 이용해 기업체의 데이터베이스나 응용 프로그램의 운영 중에 생기는 많은 데이터들에 대한 정보 교환 형태의 표준 데이터 타입을 제공해 줄 수가 있다. 따라서 대용량 XML 데이터의 효율적인 관리와 보안의 필요성이 점차 중요시되어 XML에 관한 안전한 접근 제어 기법을 개발하는 일은 새로운 방법을 필요로 하고 있다. 본 논문에서는 접근 권한부여 정책들을 정의하여 접근 제어 시스템을 설계한다. 실험 결과, 본 논문에서 제안하는 알고리즘이 기존의 접근 제어기술에서 복잡한 권한의 평가 과정으로 시스템 성능이 저하되는 문제점이 개선되었다. 따라서 본 논문에서 제안한 안전한 XML 접근 제어 정책이 기존의 접근 제어 방법보다 향상되었음을 보여주었다.